Optimization and validation of an extraction method and HPAEC-PAD for determination of residual sugar composition in l-lactic acid industrial fermentation broth with a high salt content. Issue 21 (30th September 2015) - Lv, Xiangyun; Guo, Yuanxin; Zhuang, Yingping; Wang, Yonghong
Abstract : A new HPAEC-PAD method with an off-line sample clean-up procedure has been developed for the determination of residual sugar composition inl -lactic acid industrial fermentation broth with a high salt content. Abstract : In the production ofl -lactic acid, the residual sugar in fermentation broth would lead to increased sugar content in its commercial products, bringing about lactic acid deterioration because of Maillard reactions and thus shortening their shelf life. In this work, the residual sugar components inl -lactic acid industrial fermentation broth with agricultural biomass-derived sugar were determined by means of high-performance anion-exchange chromatography (HPAEC) coupled with pulsed amperometric detection (PAD). A feasible off-line sample clean-up procedure consisting of sodium oxalate extraction, ethanol extraction and ion-exchange column extraction was developed to remove calcium ions, proteins, anion acids and organic acids before analysis, and their removal efficiencies were 100, 98.74, 97.99 and 99.41%, respectively. Under the optimized analytical conditions, the seventeen sugars, including four monosaccharides, eight disaccharides and five oligosaccharides, have been completely separated in one experimental run on a Dionex Carbopac PA 200 column with sodium hydroxide and sodium acetate as eluents. The method was validated, with good linearity ( R 2 > 0.99), high precision (RSDs < 5.47%), and sensitive detection limits (0.35–44.61 μg L −1 ); recoveries were >86.95% for short chain carbohydrates (degree of polymerization, DP < 4), while recoveries ranged from 81.87 to 61.41% for DP4 to DP7. The method was successfully applied for analysis of the residual sugar in lactic acid broth with a salt content as high as 120 g L −1 calcium lactate, using different kinds of starch (corn starch, corn flour and cassava starch) hydrolysates as carbon sources. Isomaltose (47.97–60.43%), sucrose (17.50–29.73%) and trehalose (3.05–7.51%) were the main components of residual sugar in these broths.